Influência da recristalização no comportamento da textura cristalográfica e nas perdas magnéticas por histerese de um aço elétrico de grão não orientado (GNO) - Freitas, Francisco Nélio Costa (2011)
Non-oriented electrical steels are widely used in the manufacture of cores for electric motors being the performance of this equipment affected by the presence of crystallographic texture in these materials. In other hand, the grain size considerably affects the magnetic losses. The crystallographic texture and grain size are greatly influenced by the annealing process performed after cold rolling of these steels. Annealing promotes recrystallization in the microstructure of the material which is closely related with the crystallographic texture. The objective of this study is to evaluate the influence of recrystallization on the evolution of crystallographic texture and hysteresis magnetic losses by in non-oriented grain electrical steel with 1.28% Si that was cold rolled with reductions of 50 and 70% in an industrial plant. Samples of the material in the conditions cold rolled and partially recrystallized at 580, 585, 590, 595, 600, 605, 610, 615 and 620°C and annealed at 730°C for 12 hours (box annealing) were analyzed in the aspects of microstructure, crystallographic texture and magnetic hysteresis losses. The material was also subjected to heat treatment for grain growth and they were also evaluated with respect to the microstructure and crystallographic texture. The results showed the evolution of primary recrystallization and also the microstructure and texture when the material is subjected to final heat treatment that promotes grain growth and secondary recrystallization. The crystallographic texture has changed in the process of primary recrystallization occurred during box annealing and also in the process of secondary recrystallization after heat treatment simulating the final processing of the material. The evaluation of hysteresis magnetic losses showed that the box annealing promoted a reduction of these.